FAKTOR PENDORONG INDONESIA MENANDATANGANI KERJA SAMA INDONESIA EUROPEAN FREE TRADE ASSOCIATION-COMPREHENSIVE ECONOMIC PARTNERSHIP AGREEMENT (IE-CEPA) - Shelly Pasaribu; Ardila Putri (Jurnal Ekonomi-Qu, 2021)
Indonesia cooperates with bilateral trade agreements (BTA) with the European Free Trade Association (EFTA) which consists of Iceland, Liechtenstein, Norway, and Switzerland. This cooperation is known as the Indonesia-EFTA Comprehensive Economic Partnership Agreement (IE-CEPA) which was signed on December 16, 2018. IE-CEPA is a bilateral Indonesian agreement that grows with a long duration of negotiation between other BTAs, but the stakeholders Indonesia has the persistence to get IE-CEPA. For this research, examine what are the driving factors for Indonesia to regulate the agreement. In analyzing this research, the author uses the concept of a Bilateral Trade Agreement by Jayant Menon and uses qualitative research methods. There are two driving factors that influence both general factors and specific factors. Where in general factors, the dominant factor is disenchanment with liberalization multilateral level and Politically motivated. Meanwhile, the most dominant specific factors are sector expanding, market creating, and lobby driven